Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài

Những câu hỏi liên quan
Buddy
Xem chi tiết
Nguyễn Lê Phước Thịnh
15 tháng 8 2023 lúc 22:05

\(A=log_2\left(x^3-x\right)-log_2\left(x+1\right)-log_2\left(x-1\right)\)

\(=log_2\left(\dfrac{x^3-x}{x+1}\right)-log_2\left(x-1\right)\)

\(=log_2\left(\dfrac{x\left(x-1\right)\left(x+1\right)}{x+1}\right)-log_2\left(x-1\right)\)

\(=log_2\left(\dfrac{x\left(x-1\right)\left(x+1\right)}{\left(x+1\right)\left(x-1\right)}\right)=log_2x\)

ngo mai trang
Xem chi tiết
ngo mai trang
3 tháng 10 2015 lúc 9:39

ta có \(\left(log^b_a+log^a_b+2\right)\left(log^b_a-log_{ab}^b\right).log_b^a-1=\left(log^b_a+log^a_b+2\right)\left(log^b_a.log_b^a-log_{ab}^b.log_b^a\right)-1=\left(log^b_a+log^a_b+2\right)\left(1-\frac{1}{log_b^{ba}}log_b^a\right)-1=\left(log^b_a+log^a_b+2\right)\left(1-\frac{1}{1+log^a_b}log^a_b\right)-1=\left(log^b_a+log^a_b+2\right)\frac{1}{1+log^a_b}-1=\left(log^a_b+\frac{1}{log^a_b}+2\right)\frac{1}{1+log^a_b}-1=\frac{\left(1+log^a_b\right)^2}{log^a_b}\frac{1}{1+log^a}-1=\frac{1+log^a_b}{log_b^a}-1=\frac{1}{log_b^a}\)

nguyen thi khanh hoa
3 tháng 10 2015 lúc 11:58

 ta có:

\(\left(log^b_a+\frac{1}{log^b_a}+2\right)\left(log^b_a-\frac{1}{log^{ab}_a}\right)log^a_b-1\)\(=\frac{\left(log^b_a+1\right)^2}{log^b_a}\left(log^b_a-\frac{1}{1+log^b_a}\right)log^a_b-1\)\(=\frac{\left(log^b_a+1\right)^2}{log^b_a}\left(1-\frac{log^a_b}{1+log^b_a}\right)-1\)\(==\frac{\left(log^b_a+1\right)^2}{log^b_a}\left(\frac{1}{1+log^b_a}\right)-1=\frac{1+log^b_a}{log^b_a}-1=\frac{1}{log^b_a}\)

Nguyễn Thị Quỳnh Như
Xem chi tiết
Nguyễn Minh Hằng
4 tháng 5 2016 lúc 10:27

Ta có \(A=\left(\log^3_ba+2\log^2_ba+\log_ba\right)\left(\log_ab-\log_{ab}b\right)-\log_ba\)

             \(=\left(\log_ba+1\right)^2\left(1-\frac{1}{\log_aab}\right)-\log_ba\)

             \(=\left(\log_ba+1\right)^2\left(1-\frac{1}{1+\log_ab}\right)-\log_ba\)

             \(=\left(\log_ba+1\right)^2\left(1-\frac{\log_ba}{\log_ba+1}\right)-\log_ba\)

             \(=\log_ba+1-\log_ba=1\)

ngo mai trang
Xem chi tiết
nguyen thi khanh hoa
3 tháng 10 2015 lúc 9:50

 ta có:

\(log^{\left(2a^2\right)}_2+\left(log_2^a\right)a^{log_a^{\left(log^a_1+1\right)}}+\frac{1}{2}log^2_2a^4=log_2^2+log_2^{a^2}+log_2^a\left(log^a_2+1\right)+\frac{1}{2}log^2_2a^4\)

\(=1+2log^a_2+log^a_2\left(1+log^a_2\right)+2log^2a_2\)

\(=3log^2_2a+3log^a_2+1\)

Buddy
Xem chi tiết
Hà Quang Minh
24 tháng 8 2023 lúc 0:46

\(a,A=log_23\cdot log_34\cdot log_45\cdot log_56\cdot log_67\cdot log_78\\ =log_28\\ =log_22^3\\ =3\\ b,B=log_22\cdot log_24...log_22^n\\ =log_22\cdot log_22^2...log_22^n\\ =1\cdot2\cdot...\cdot n\\ =n!\)

James Pham
Xem chi tiết
Nguyễn Lê Phước Thịnh
18 tháng 1 2024 lúc 21:04

\(A=\left(lna+log_{\alpha}e\right)^2+ln^2a-\log_a^2e\)

\(=ln^2a+\log_{\alpha}^2e+2\cdot lna\cdot\log_{\alpha}e+ln^2a-\log_{\alpha}^2e\)

\(=2\cdot\log_e^2\alpha+2\cdot\log_e\alpha\cdot\log_{\alpha}e\)

\(=2\cdot ln^2\alpha+2\)

Minh Anh
Xem chi tiết
Buddy
Xem chi tiết
Nguyễn Lê Phước Thịnh
18 tháng 8 2023 lúc 23:10

a: \(log_49=\dfrac{log9}{log4}=\dfrac{log3^2}{log2^2}=\dfrac{2\cdot log3}{2\cdot log2}=\dfrac{log3}{log2}=\dfrac{b}{a}\)

b: \(log_612=\dfrac{log12}{log6}=\dfrac{log2^2+log3}{log2+log3}=\dfrac{2\cdot log2+log3}{log2+log3}\)

\(=\dfrac{2a+b}{a+b}\)

c: \(log_56=\dfrac{log6}{log5}=\dfrac{log\left(2\cdot3\right)}{log\left(\dfrac{10}{2}\right)}=\dfrac{log2+log3}{log10-log2}\)

\(=\dfrac{a+b}{1-a}\)

Nguyễn Huy Hoàng
22 tháng 1 lúc 21:22

a: l o g 4 9 = l o g 9 l o g 4 = l o g 3 2 l o g 2 2 = 2 ⋅ l o g 3 2 ⋅ l o g 2 = l o g 3 l o g 2 = b a log 4 ​ 9= log4 log9 ​ = log2 2 log3 2 ​ = 2⋅log2 2⋅log3 ​ = log2 log3 ​ = a b ​ b: l o g 6 12 = l o g 12 l o g 6 = l o g 2 2 + l o g 3 l o g 2 + l o g 3 = 2 ⋅ l o g 2 + l o g 3 l o g 2 + l o g 3 log 6 ​ 12= log6 log12 ​ = log2+log3 log2 2 +log3 ​ = log2+log3 2⋅log2+log3 ​ = 2 a + b a + b = a+b 2a+b ​ c: l o g 5 6 = l o g 6 l o g 5 = l o g ( 2 ⋅ 3 ) l o g ( 10 2 ) = l o g 2 + l o g 3 l o g 10 − l o g 2 log 5 ​ 6= log5 log6 ​ = log( 2 10 ​ ) log(2⋅3) ​ = log10−log2 log2+log3 ​ = a + b 1 − a = 1−a a+b ​

Vũ Hiền Vi
Xem chi tiết
Nguyễn Trọng Nghĩa
4 tháng 5 2016 lúc 16:51

\(R=\log_22x^2+\left(\log_2x\right)x^{\log_x\left(\log_2x+1\right)}+\frac{1}{2}\log^2_4x^4\)

    \(=1+2\log_2x+\left(\log_2x\right)\left(\log_2x+1\right)+2\log^2_2x\)

    \(=3\log^2_2x+3\log_2x+1\)

Buddy
Xem chi tiết
HT.Phong (9A5)
18 tháng 8 2023 lúc 18:21

a) \(log_69+log_64=log_636=2\)

b) \(log_52-log_550=log_5\left(2:50\right)=-2\)

c) \(log_3\sqrt{5}-\dfrac{1}{2}log_550=-1,0479\)